Autonomic Nervous System Dysfunction in Patients With Parkinson Disease Having Depression. (January 2016) - Park, Hyung-Eun; Kim, Joong-Seok; Oh, Yoon-Sang; Park, In-Seok; Park, Jeong-Wook; Song, In-Uk; Lee, Kwang-Soo
Background and Aim: Both depression and cardiovascular autonomic dysfunctions, such as orthostatic hypotension, supine hypertension, and the absence of normal nocturnal blood pressure (BP) fall ("nondipping"), occur relatively commonly in Parkinson disease (PD); however, the relationship between depression and cardiovascular autonomic abnormalities has not been established. In this study, we sought to determine whether the cardiovascular autonomic abnormalities found in PD are associated with depression. Methods: Among 129 nondemented, levodopa-naive patients with mild PD, 44 had depression. Orthostatic vital signs and ambulatory 24-hour BP monitoring were recorded, and geriatric depressive scales were obtained in all patients. Associations between orthostatic hypotension, supine hypertension, nocturnal hypertension, nondipping, and depression were analyzed. The ratio of the standard deviation of 24-hour heart rate to that of systolic BP (SBP) was utilized as an index of baroreflex–cardiovagal function. Results: Depression was associated with orthostatic hypotension, and patients with depression had higher SBP change during orthostasis and attenuated cardiovagal dysfunction as observed during ambulatory BP monitoring. Across individuals, values for orthostatic changes in BP were correlated with values for geriatric depressive scale. Conclusion: Depression is associated with neurocirculatory abnormalities—especially orthostatic hypotension—in early PD. Although the association does not imply causation, this result suggests that depression in PD might be associated with functional impairment of the autonomic nervous system and its pathologic substrate.